1995
DOI: 10.12693/aphyspola.87.500
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Study of Photoluminescence from Deep CdTe/Cd1-xMnxTe Quantum Wells

Abstract: The photoluminescence studies in CdTe/CdMnTe quantum wells are reported in the temperature range 10-300 K. The MnTe concentration in the barriers is x = 0.3, 0.5, 0.63 and 0.68. Thus the potential wells in our samples are very deep, of the order of 800 meV in the conduction band and 200 meV in the valence band in the case of the x = 0.68 sample. In spite of the large lattice mismatch (related to high x value) between the wells and the barriers the observed line widths are as narrow as 2 meV in the case of 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
4
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
3
4
0
Order By: Relevance
“…This iS in good agreement with more accurate spectral discrimination in Ref. [9]. The curves shown in Fig.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…This iS in good agreement with more accurate spectral discrimination in Ref. [9]. The curves shown in Fig.…”
supporting
confidence: 89%
“…This finding is in agreement with the conclusion of the time resolved luminescence study of Polhman et al [2] who showed that in shallow Cd1-x MnxTe quantum wells only the low temperature (below 50 K) luminescence decay is limited by radiative recombination of excitons while at high temperatures τi is due to non-radiative recombination. Our conclusion concerning the non-radiative character of the mechanism which determines the luminescence decay at 300 K is also compatible with the fast decrease in the spectrally integrated intensity of the luminescence with increasing temperature found in [9] in this highest temperature range.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Also, an enhanced paramagnetic contribution to the magnetic susceptibility at low temperatures has been found in CdTe/CdMnTe superlattice. The latter effect was assigned to the presence of isolated paramagnetic ions in the interface regions as a result of an intermixing of Mn and Cd ions and/or a smaller number of magnetic bonds at the interface.In this paper we report results of magnetic measurements performed on both thick (Cd 0.60 Mn0.40 Τe and MnTe) epilayer and CdTe/Cd 0.50Mn0.50 Te superlattices grown by MBE on GaAs substrates [3]. In order to reduce effects of (169)…”
mentioning
confidence: 99%
“…In this paper we report results of magnetic measurements performed on both thick (Cd 0.60 Mn0.40 Τe and MnTe) epilayer and CdTe/Cd 0.50Mn0.50 Te superlattices grown by MBE on GaAs substrates [3]. In order to reduce effects of (169) the lattice mismatch, GaAs was buffered with 3 μm of CdTe.…”
mentioning
confidence: 99%